Some thermodynamic effects in thin film adhesion - Chornous, A.M.; KirikI, G.V.; Protsenko, Yu.; Stadnik, A.D. (Functional Materials, 2005)
The following thermodynamic effects have been studied in experiment: the normal adhesion of Ge films as a function of the surface energy of substrate (glass, mica, Al, Cu); the normal adhesion of Ge, Al, Cu and Cr films to Cu and (001) NaCI substrates as a function of the specific surface energy of the film; the dimensional dependence of Cu and Cr adhesion within thickness range of 20 to 250 nm; effect of finely dispersed ferromagnetic and weakly magnetic powders used as fillers in partially crystallized polymer substrates with relatively low specific surface energy on Al film adhesion. An increase in the film thickness as well as in the specific surface energy of the substrate and the film has been found to result in weakened adhesion. Экспериментально изучены следующие термодинамические эффекты: зависимость нормальной адгезии пленок Ge от удельной поверхностной энергии подложки (стекло, слюда, AI, Си); зависимость нормальной адгезии от удельной поверхностной энергии пленки (Ge, Al, Си и Cr) на подложках Си и (001) NaCI; размерная зависимость адгезии пленок Си и Сг в интервале толщин 20—250 нм; влияние наполнения частично-кристаллических полимерных подложек с относительно малой удельной поверхностной энергией мелкодисперсными ферро- и слабомагнитными порошками на адгезию пленок AI. Установлено, что увеличение толщины пленки, удельной поверхностной энергии подложки или пленки приводит к уменьшению адгезии. Експериментально вивчено такі термодинамічні ефекти: залежність нормальної адгезії плівок Ge від питомої поверхневої енергії підкладки (скло, слюда, Al, Cu); залежність нормальної адгезії від питомої поверхневої енергії плівки (Ge, Al, Cu і Сг) на підкладках Cu і (001) NaCI; розмірна залежність адгезії плівок Cu і Сг в інтервалі товщин 20—250 нм; вплив наповнення частково-кристалічних полімерних підкладок з відносно малою поверхневою енергією мілкодисперсними феро- та слабкомагнітними порошками на адгезію плівок АІ. Встановлено, що збільшення товщини плівки, питомої поверхневої енергії підкладки або плівки призводить до зменшення адгезії.